(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The following article examines the post Covid digital transformation in tourism distribution channels. Its focus is on the shift in consumers preferences when choosing and booking a trip, because of the integration of technological innovations. The analysis includes the questions: where do consumers acquire information about the tourism products offers when choosing a destination, an accommodation and a transport mean before and after the pandemic; what are their motives for choosing a tourism product; what are the main characteristics (geographic, demographic, socio-economic, geodemographic and psychographic) of consumers that influence the decision to reserve a tourism product and how do they carry out the process of booking tourism products after the Covid-19 pandemic. Scientific research in the field of e-commerce and in tourism marketing channels over the last three years has been focused either on digital transformations in the industry or on the shift in consumers` preferences after the Covid-19 pandemic. However, there is a lack of in-depth scientific research on the post-Covid digital transformation of tourism marketing channels in Bulgaria. The significance of the topic for the EU tourism policy, for the Bulgarian tourism sector and for local authorities and destination management organizations and the gap in research on the changes in consumer preferences after the pandemic in Bulgaria gave me a reason to focus on this study.